'Chemistry at the speed of sound': automated 1536-well nanoscale synthesis of 16 scaffolds in parallel. Issue 4 (24th January 2023) - Gao, Li; Shaabani, Shabnam; Reyes Romero, Atilio; Xu, Ruixue; Ahmadianmoghaddam, Maryam; Dömling, Alexander
Abstract : Sustainable synthesis of highly diverse screening libraries of small molecules. Abstract : Screening of large and diverse libraries is the 'bread and butter' in the first phase of the discovery of novel drugs. However, maintenance and periodic renewal of high-quality large compound collections pose considerable logistic, environmental and monetary problems. Here, we exercise an alternative, the 'on-the-fly' synthesis of large and diverse libraries on a nanoscale in a highly automated fashion. For the first time, we show the feasibility of the synthesis of a large library based on 16 different chemistries in parallel on several 384-well plates using the acoustic dispensing ejection (ADE) technology platform. In contrast to combinatorial chemistry, we produced 16 scaffolds at the same time and in a sparse matrix fashion, and each compound was produced by a random combination of diverse large building blocks. The synthesis, analytics, resynthesis of selected compounds, and chemoinformatic analysis of the library are described. The advantages of the herein described automated nanoscale synthesis approach include great library diversity, absence of library storage logistics, superior economics, speed of synthesis by automation, increased safety, and hence sustainable chemistry.